Impurity-induced triple point fermions in twisted bilayer graphene - Ramires, Aline [UNESP]; Lado, Jose L. (American Physical Society (APS), 2019)
Triple point fermions are elusive electronic excitations that generalize Dirac and Weyl modes beyond the conventional high-energy paradigm. Yet, finding real materials naturally hosting these excitations at the Fermi energy has remained challenging. Here we show that twisted bilayer graphene is a versatile platform to realize robust triple point fermions in two dimensions. In particular, we establish that the introduction of localized impurities lifts one of the two degenerate Dirac cones, yielding triple point fermions at charge neutrality. Furthermore, we show that the valley polarization is preserved for certain impurity locations in the Moiré supercell for both weak and strong impurity potentials. We finally show that in the presence of interactions, a symmetry-broken state with local magnetization can develop out of the triple point bands, which can be selectively controlled by electrostatic gating. Our results put forward twisted bilayer graphene as a simple solid-state platform to realize triple point fermions at charge neutrality and demonstrate the nontrivial role of impurities in Moiré systems.